IMPLEMENTATION OF MADRASAH PRINCIPAL DECISION MAKING AT MA MA’ARIF NU LUMAJANG - Rosyida, Fatia Ainur; Hanifah, Khusnul; Barizi, Ahmad (Idaarah: Jurnal Manajemen Pendidikan, 2024)
This research aims to determine and describe the process, supporting factors and obstacles to decision making in implementing the tahfidzul Qur’an program at MA Ma’arif NU Lumajang. This research method uses descriptive qualitative methods. Meanwhile, data collection was obtained from interviews, observation and documentation. The results of the research show that the decision-making process in implementing the tahfidzul Qur’an program consists of several stages, namely identifying problems, holding meeting1s with school stakeholders, forming a tahfidzul Qur’an management team, preparing a tahfidzul Qur’an activity program, holding outreach with parents/ parents, make a black and white agreement. The supporting factors are that stakeholders participate fully, obtain approval from several parents/guardians, there are several teachers who have expertise in the field of the Koran. Meanwhile, inhibiting factors include disapproval from some parents/guardians and the number of administrators of the tahfidzul Qur’an program is still limited. Therefore, the role of the Madrasah Head determines the progress and development of the institution.